Elevated TG/HDL-C ratio is an independent predictor of outcome and it is associated with CAD progression in patients with stable coronary artery disease. (25th November 2020) - Caselli, C; Rocchiccioli, S; Smit, J.M; Ragusa, R; Rosendael, R; Buechel, R; Teresinska, A; Pizzi, M.N; Magnacca, M; Campolo, J; Knuuti, J; Parodi, O; et al.
Abstract: Background: Elevated TG/HDL-C ratio is associated with CVD outcomes in high-risk populations presenting for coronary angiography, but studies were limited in gender-specific populations or in pts with ACS. Purpose: Aim of this study was to evaluate the prognostic role of TG/HDL-C levels and their association with CAD progression in pts with suspected stable CAD. Methods: TG/HDL-C ratio was calculated in 545 pts (60±9yrs, 330males) with symptoms of stable CAD enrolled in the EVINCI study. 490 pts underwent coronary CTA to assess the presence of CAD (>50%stenosis) and entered a clinical follow up (4.5±0.9yrs). The CVD outcome measure included all cause mortality, non fatal MI, hospitalization for unstable angina or HF. After 6±1yrs, during the SMARTool study, a second CTA was obtained in 171 EVINCI pts and a CTA risk score (based on plaque extent, severity, composition, and location) was calculated at enrolment and at follow up to assess CAD progression (ΔCTA score). Results: Pts were divided according to TG/HDL-C quartiles: IQ (<1.32), IIQ (1.32–2.03), IIIQ (2.04–3.33), and IVQ (>3.33). As reported in Table, the frequency of male, diabetes, metabolic syndrome and obesity increased among quartiles. Glucidic biomarkers progressively increased from quartile I to IV, while LDL-C decreased. The prevalence of obstructive CAD at CTA did not differ among groups. The CVD endpoint occurred in 7% of pts. At multivariable analyses, high TG/HDL-C ratio (IVQ) was associated with the outcome endpoint independently from presence of obstructive CAD and treatment (HR 3.477, 95% CI 1.181–10.239, P=0.0237). CTA score was significantly higher in pts in IVQ compared to IQ at both SMARTool enrolment and follow up (Figure1). A significantly higher ΔCTA score was observed in pts in III-IVQ compared with those in I-IIQ (Figure2). Conclusion: Elevated TG/HDL-C ratio is an independent predictor of outcome and it is associated with CAD progression in patients with stable CAD. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): "EValuation of INtegrated Cardiac Imaging" - EVINCI [GA number: 222915]; "Simulation Modeling of coronary ARTery disease: a tool for clinical decision support - SMARTool" [GA number: 689068]